Multi-omics analysis reveals the effects of host-rumen microbiota interactions on growth performance in a goat model - Chen, Juncai; Zhang, Xiaoli; Chang, Xuan; Wei, Bingni; Fang, Yan; Song, Shanshan; Gong, Daxiang; Huang, Deli; Sun, Yawang; Dong, Xianwen; Zhao, Yongju; Zhao, Zhongquan (Frontiers in Microbiology, 2024)
The growth rate of young ruminants has been associated with production performance in later life, with recent studies highlighting the importance of rumen microbes in supporting the health and growth of ruminants. However, the specific role of rumen epithelium bacteria and microbiota-host interactions in influencing the early life growth rate of ruminants remains poorly understood. In this study, we investigated the rumen fermentation pattern, microbiota characteristics, and global gene expression profiles of the rumen epithelium in 6-month-old goats with varying growth rates. Our results showed that goats with high average daily gain (HADG) exhibited higher rumen propionate concentrations. Goats with low average daily gain (LADG) had the higher relative abundances of rumen epithelium bacteria genera U29-B03 and Quinella, while exhibiting a lower relative abundance of Lachnospiraceae UCG-009. In the rumen fluid, the relative abundances of bacteria genus Alloprevotella were lower and Desulfovibrio were higher in LADG goats compared to HADG goats. Additionally, the relative abundance of fungal genus Symmetrospora was lower in LADG goats compared to HADG goats. Transcriptome analysis showed that 415 genes were differentially expressed between LADG and HADG goats, which were enriched in functions related to cell junction and cell adhesion, etc. Correlation analysis revealed that rumen epithelium bacteria genera UCG-005 and Candidatus Saccharimonas were negatively associated, while Lachnospiraceae NK3A20 group and Oscillospiraceae NK4A214 group were positively associated with average daily gain (ADG) and genes related to barrier function. The rumen fluid bacteria genus Alloprevotella was positively correlated, while Desulfovibrio was negatively correlated with rumen propionate and ammoniacal nitrogen (NH3-N) concentrations, as well as genes related to barrier function and short chain fatty acids (SCFAs) transport. In summary, our study reveals that the higher ruminal fermentation efficiency, improved rumen epithelial barrier functions, and enhanced SCFAs transport in HADG goats could be attributed to the rumen microbiota, particularly the rumen epithelium bacteria, such as Lachnospiraceae and Oscillospiraceae NK4A214 group.